Boosting hydrogen evolution on MoS2 via co-confining selenium in surface and cobalt in inner layer - Zhilong Zheng (Nature Portfolio, 2020)
The lack of efficient, inexpensive catalysts hinders large-scale application of hydrogen evolution reaction (HER). Here, the authors report a MoS2 nanofoam catalyst with co-confined Se in the surface and Co in the inner layer, exhibiting high large-current-density HER activity and durability.